2022
DOI: 10.3389/fonc.2022.853038
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends in Death, Years of Life Lost, and Years Lived With Disability Caused by Breast Cancer Attributable to Secondhand Smoke From 1990 to 2019

Abstract: BackgroundSecondhand smoke is an important risk factor to breast cancer patients’ survival. This article aimed to describe the epidemiological changes of health loss caused by female breast cancer attributable to secondhand smoke from 1990 to 2019.MethodsData on breast cancer was derived from the Global Burden of Disease study 2019. The epidemiological status and trends were estimated using the number, age-standardized rate (ASR), and estimated annual percentage change (EAPC).ResultsIn 2019, secondhand smoke-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, this was not the aim of this study and would create complexity to the easy to interpret risk charts that already account for the most important risk factors. It could also be useful to estimate the 10-year risk of breast cancer in women by smoking status, as some studies found an association of passive and active smoking with higher risk of breast cancer ( 41 ). However, currently available risk estimates for exposure to tobacco and breast cancer differs by factors such as age at starting smoking relative to age at menarche and family history of breast cancer, and we did not have data available on this.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not the aim of this study and would create complexity to the easy to interpret risk charts that already account for the most important risk factors. It could also be useful to estimate the 10-year risk of breast cancer in women by smoking status, as some studies found an association of passive and active smoking with higher risk of breast cancer ( 41 ). However, currently available risk estimates for exposure to tobacco and breast cancer differs by factors such as age at starting smoking relative to age at menarche and family history of breast cancer, and we did not have data available on this.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SHS in the risk of cancer in non-smokers has been investigated mainly for lung cancer, with considerably less data on other cancer sites. Except for the aforementioned breast cancer, exposure to passive smoking was independently associated with an increased risk of nasopharyngeal, laryngeal, and cervical cancer [ 32 , 33 , 34 , 35 ]. Moreover, SHS also predisposes to a higher cardiovascular (CV) morbidity.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%